Design and synthesis of hierarchical NiCo2S4@NiMoO4 core/shell nanospheres for high-performance supercapacitors. (27th August 2015) - Yao, Mingming; Hu, Zhonghua; Liu, Yafei; Liu, Peipei
Abstract : A novel electrode material of three-dimensional hierarchical NiCo2 S4 @NiMoO4 core/shell nanospheres was synthesized by a facile two-step hydrothermal method. These hierarchical NiCo2 S4 @NiMoO4 core/shell nanospheres exhibit a high specific capacitance of 1714 F g −1 at a current density of 1 A g −1, which indicated the excellent electrochemistry performance. Abstract : A novel electrode material of three-dimensional (3D) hierarchical NiCo2 S4 @NiMoO4 core/shell nanospheres for high-performance supercapacitors was successfully synthesized by a two-step method. First, ball-like NiCo2 S4 was obtained by controlling the morphology through a hydrothermal method using diethanol amine as a new precipitant; second, the interconnected uniform NiMoO4 nanosheets were allowed to efficiently grow on the NiCo2 S4 backbone by the hydrothermal method to form NiCo2 S4 @NiMoO4 core/shell nanospheres. The resultant hierarchical NiCo2 S4 @NiMoO4 core/shell nanospheres were characterized by X-ray diffraction, energy dispersive spectrometry, X-ray photoelectron spectroscopy, field-emission scanning electron microscopy, transmission electron microscopy and N2 adsorption and desorption. The electrochemical properties of the samples were evaluated though cyclic voltammetry, charge–discharge and electrochemical impedance spectroscopy in 6.0 M KOH electrolytic solution. The results showed that the hierarchical NiCo2 S4 @NiMoO4 core/shell nanospheres exhibited a very large specific capacitance of 1714 F g −1 at 1 A g −1, an outstanding cyclic stability with a capacitance retention of 96% after 5000 cycles of charge–discharge and a low resistance.